Bibliometric analysis of metformin as an immunomodulator (2013–2024) - Zhou, Tongyi; Yu, Yunfeng; Li, Liu; Liu, Xiu; Xiang, Qin; Yu, Rong (Frontiers in Immunology, 2025)
BackgroundMetformin, the frontline treatment for diabetes, has considerable potential as an immunomodulator; however, detailed bibliometric analyses on this subject are limited.MethodsThis study extracted 640 relevant articles from the Web of Science (WOS) Core Collection and conducted visual analyses using Microsoft Excel, VOSviewer, and CiteSpace.ResultsThe findings showed that research on the immunomodulatory function of metformin has grown steadily since 2017, with China and the United States being the leading contributors. These studies have mostly been published in journals such as the International Journal of Molecular Sciences, Cancers, Frontiers in Immunology, and Scientific Reports. Keyword co-occurrence analysis highlighted metformin’s role as an immunomodulator, particularly in the context of the tumor immune microenvironment, immunosuppressive checkpoints, and metformin derivatives. Recent research has highlighted metformin’s application in aging, autoimmune diseases, COVID-19, and tuberculosis. Additionally, its role in regulating inflammation and gut microbiota is also being investigated.ConclusionOverall, the immunomodulatory effects of metformin were investigated in anti-tumor, antiviral, anti-aging, and autoimmune disease research. This highlights the scope of metformin use in these fields, while also significantly enhancing its clinical value as a repurposed drug.